The Role of Leadership in Managing Risk to Ensure Project Success in the Arabian American Oil Company (Aramco) In Saudi Arabia from 2020 to 2024 - Qablawi, Badr Rashad; Abuttahir, Rawda Ayman (Journal of Risk and Crisis Management, 2025)
This comprehensive study examines the pivotal role of leadership in managing risks and ensuring project success within Saudi Aramco, a global leader in the oil industry, during the period from 2020 to 2024. The research focuses on two predominant leadership styles—transformational and transactional—and their impact on organizational resilience and risk management strategies. By addressing these leadership factors, the study aims to understand how effective leadership can mitigate risks and enhance the success of large-scale projects. The research problem centers on the increasing importance of risk management in a rapidly changing business environment, particularly in the context of Saudi Aramco’s operations. As the organization plays a crucial role in the global oil supply chain, the ability to manage risks effectively is essential for maintaining operational continuity and achieving strategic objectives. This study is particularly significant as it aligns with Saudi Arabia’s Vision 2030, which emphasizes the need for robust leadership to drive economic diversification and growth. The study’s objectives include identifying leadership traits that contribute to effective risk management, evaluating the influence of different leadership styles on organizational resilience, and recommending strategies to enhance leadership practices within the organization. The research is guided by four hypotheses that explore the relationship between leadership styles and risk management outcomes, focusing on how these dynamics influence project success. A qualitative research methodology was employed, utilizing in-depth interviews and thematic analysis to gather data from 100 participants within Saudi Aramco. The interviews focused on leaders’ approaches to risk management, the challenges they face, and the strategies they use to foster organizational resilience. The analysis of this data revealed significant insights into how transformational and transactional leadership styles affect risk management practices and organizational outcomes. The results confirmed all four hypotheses, demonstrating that transformational leadership positively impacts organizational resilience and risk management effectiveness, while transactional leadership provides a structured approach to risk management.